Comments on the Mechanism of Detachment in Creep of Dispersion Strengthened Alloys at High Temperatures - Michael E. Kassner; Theophil Oros; Praveen Kumar (Metals, 2022)
This short article comments on the interactions between incoherent hard particles and dislocations, in dispersion-strengthened alloys, at elevated temperatures, which is the basis for their strength at high temperatures. We briefly review the details of the detachment model, discuss the limitations of the models and propose a new model for detachment. The purpose of this communication is to finally offer the creep research community a detailed mechanism for the dislocation detachment from hard particles, which has not yet been formulated.